2003
DOI: 10.1016/s0092-8674(03)01017-1
|View full text |Cite
|
Sign up to set email alerts
|

A Key Role for TRPM7 Channels in Anoxic Neuronal Death

Abstract: Excitotoxicity in brain ischemia triggers neuronal death and neurological disability, and yet these are not prevented by antiexcitotoxic therapy (AET) in humans. Here, we show that in neurons subjected to prolonged oxygen glucose deprivation (OGD), AET unmasks a dominant death mechanism perpetuated by a Ca2+-permeable nonselective cation conductance (IOGD). IOGD was activated by reactive oxygen/nitrogen species (ROS), and permitted neuronal Ca2+ overload and further ROS production despite AET. IOGD currents co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
756
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 717 publications
(790 citation statements)
references
References 41 publications
32
756
0
2
Order By: Relevance
“…A transient increase of mitochondrial fusion after acute neuronal insult could possibly protect cells from excitotoxicity. Both our group and Barsoum et al have shown that fusion protects against ROS [30,76], which can also lead to Ca 2+ influx through TRMP7 channels [125]. In contrast to neuronal cell death, in HeLa cells mitochondrial fission can protect against death induced by the propagation of Ca 2+ waves along the mitochondria [126].…”
Section: The Role Of Mitochondrial Fusion In Cell Death: Mfn1 and Mfnmentioning
confidence: 83%
See 1 more Smart Citation
“…A transient increase of mitochondrial fusion after acute neuronal insult could possibly protect cells from excitotoxicity. Both our group and Barsoum et al have shown that fusion protects against ROS [30,76], which can also lead to Ca 2+ influx through TRMP7 channels [125]. In contrast to neuronal cell death, in HeLa cells mitochondrial fission can protect against death induced by the propagation of Ca 2+ waves along the mitochondria [126].…”
Section: The Role Of Mitochondrial Fusion In Cell Death: Mfn1 and Mfnmentioning
confidence: 83%
“…Indeed, Opa1 overexpression rescues cell death by maintaining Fig. 3 Activation of the mitochondrial fusion protein Mfn2 or inhibition of the fission protein Drp1 can enhance mitochondrial fusion in cortical neurons, which can protect mitochondria from fragmentation during neuronal cell death induced by oxidative stress (H 2 O 2 ) and subsequently, inhibition of cell death [125]. Cortical neurons from E15.5 mice were infected with the indicated construct via adenoviral vector at the time of plating.…”
Section: Mitochondrial Cristae Structure and Cell Death: Demolition Fmentioning
confidence: 99%
“…A further role of TRPM7 in neuronal cells has been suggested by Aarts et al (2003), who subjected cultured cortical neurons to prolonged oxygen and glucose deprivation (OGD), an experimental model for ischemia that causes anoxic cell death. OGD caused significant influx of Ca 2+ that correlated with the amount of cell death.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…For instance, two genes essential for sensory physiology, TRPV1 and Drosophila TRPL, were found to be only slightly more permeable to Ca 2+ than to Mg 2+ (Caterina et al 1997;Reuss et al 1997). Finally, two recent reports suggest that TRPM7-mediated Ca 2+ influx is involved in anoxic neuronal cell death and in regulation of the cell cycle of human retinoblastoma cells (Aarts et al 2003;Hanano et al 2004). Thus, additional experiments are required to elucidate whether the biological role of TRPM6 and TRPM7 channels is restricted to Mg 2+ homeostasis.…”
Section: Trpm6 and Trpm7 Channel Subunits And Their Complexesmentioning
confidence: 99%